Where Can Arts Integration Go? HOPE, Chess, and Ancient Viruses - Sameshima, Pauline (Art/Research International, 2025)
This article draws attention to the evolution of arts integrated research from the academic margins to broader acceptance by documenting the use of arts integrated research within The HOPE Collaboratory, a global initiative pursuing an HIV cure through the block-lock-stop (BLS) strategy. It highlights the HOPE Community Arts Integrated Research (CAIR) program’s role in fostering community engagement, empathy, inclusion, and hope; enhancing scientific communication and public education; and promoting collaborative knowledge creation for reparative and residual research possibilities. Using the Parallaxic Praxis framework, the project demonstrates how art—through poetry, visual installations, social media, and participatory events—makes complex scientific concepts accessible, amplifies the voices of those affected by HIV, and bridges connections among researchers, communities, and the public. As an example, the article also documents the pedagogical and research significance of the Ecosystem chessboard artwork, a permanent exhibit at four international research sites.